Preliminary Design of the Electrical Power Systems for DTT Nuclear Fusion Plant - Marzia Caldora; Maria Carmen Falvo; Alessandro Lampasi; Gianluca Marelli (Applied Sciences, 2021)
The realization of the Divertor Tokamak Test (DTT) facility is one of the key milestones of the European Roadmap, aiming to explore alternative power exhaust solutions for DEMO, the first nuclear-fusion power plant that will be connected to the European grid. For the actual implementation of the DTT and DEMO plants, it is necessary to define the structure of the internal electric power distribution system, able to supply unconventional loads with a sufficient level of reliability. The present paper reports the preliminary studies for the feasibility and realization of the electrical power systems of DTT, describing the methodology adopted to obtain a first distribution configuration and providing some simulation results. In particular, the first stage of the study deals with the survey and characterization of the electrical loads, which allows defining a general layout of the facility and size the main electrical components. To verify the correctness of the assumptions, simulation models of the grid were implemented in the DIgSILENT PowerFactory software in order to carry out power flow and fault analyses.